Hydrogen sulfide improves endothelial dysfunction by inhibiting the vicious cycle of NLRP3 inflammasome and oxidative stress in spontaneously hypertensive rats. Issue 8 (August 2019) - Li, Jiabao; Teng, Xu; Jin, Sheng; Dong, Jinghui; Guo, Qi; Tian, Danyang; Wu, Yuming
Abstract : Objective: To elucidate whether by inhibiting inflammasome and oxidative stress, hydrogen sulfide (H2 S) can ameliorate endothelial dysfunction with hypertension. Methods: Spontaneously hypertensive rats (SHR) and normotensive Wistar–Kyoto rats (WKY) were injected with 100 μmol/l sodium hydrosulfide (NaHS) intraperitoneally daily for 16 weeks. SBP and plasma malondialdehyde (MDA) and interleukin 1β (IL-1β) levels were measured. Renal vascular function was used to determine endothelial-dependent contraction (EDC) and endothelial-dependent relaxation (EDR). Protein levels of NOX1, p67 Phox, Nrf2, SOD1, CAT, NLRP3, caspase-1 and IL-1β were detected by western blot analysis. Human umbilical vein endothelial cells (HUVECs) were used to confirm the protective role of H2 S against angiotensin II (Ang II)-induced cell injury. Results: Exogenous NaHS administration significantly reduced SBP and ameliorated damaged EDC and EDR. H2 S reduced the activation of NLRP3 inflammasome and oxidative stress in SHR. The endothelial protective and antioxidant effect of H2 S was abolished by lipopolysaccharide, an inducer of NLRP3 inflammasome. In HUVECs, H2 S significantly ameliorated Ang II-induced cellular impairment, NLRP3 inflammasome activity and reactive oxygen species generation. After knocking down Nrf2, the protective effect of H2 S was abolished. Conclusion: H2 S could inhibit the vicious cycle of oxidative stress and inflammation in hypertension, and then improve endothelial function and ameliorated hypertension. Our results help to reveal the crucial role of H2 S in regulating endothelial function, which might be a new tool for treating hypertension.